(untitled) (Reflection and Critique Law Magazine, 2020)
The present article deals with the question regarding whether there is a right answer in law, from the methodological perspective of Karl Popper. It will be analyzed the Popper’s Hypothetical-Deductive Method, within a process of rupture with the positivism and the inductive method. Next, after demonstrating the existing theories about the right answer, the theme will be analyzed from the perspective of Critical Rationalism, which will lead us to the conclusion that it is impossible to reach the right answer, although this concept should be used as a parameter for the elaboration of rational and justifiable judicial decisions that are compatible with the Constitution.